Rituximab alone as induction therapy for membranous lupus nephritis: A multicenter retrospective study. Issue 27 (July 2017) - Chavarot, Nathalie; Verhelst, David; Pardon, Agathe; Caudwell, Valérie; Mercadal, Lucile; Sacchi, Antoinette; Leonardi, Catherine; Le Guern, Véronique; Karras, Alexandre; Daugas, Eric
Abstract : Abstract: The optimal treatment for pure membranous lupus nephritis (MLN) remains undetermined. Rituximab constitutes a promising therapeutic option for lupus nephritis and is currently being evaluated for use in idiopathic membranous nephritis. We retrospectively analysed the efficacy and tolerance of rituximab as a monotherapy in the induction treatment of pure MLN. We retrospectively investigated SLE patients with biopsy-proven pure class V lupus nephritis presenting with a protein-to-creatinine ratio of at least 2 g/g and treated with rituximab as monotherapy. A background low dose of corticosteroids (⩽20 mg/day) was allowed, as was hydroxychloroquine; higher doses of steroids and/or immunosuppressive drugs fell under the exclusion criteria. Remission status was evaluated at baseline and 6, 12, and 24 months after rituximab. The study included 15 patients (13 women, median age 37 years, 27% with extra-renal manifestations, median SLE duration 1.5 years). The median protein-to-creatinine ratio was 4.9 g/g, 80% of the patients had nephrotic-range proteinuria, the median serum albumin was 24 g/L, the median serum creatinine was 0.7 mg/dL, and the median eGFR was 122 mL/min/1.73 m 2 . The median follow-up was 29 months (6–112 months). Treatment failure occurred in 2 patients. However, remission was recorded in the remaining 13 (87%, complete remission in 8 patients) with a median time to remission of 5 months. Median proteinuria decreased from 4.9 g/g to 0.16 g/g at month 12 and to 0.11 g/g at month 24. Median serum albumin increased to 36.5 g/L at month 24, and all patients had serum albumin levels greater than 30 g/L at month 12. Renal function remained stable in all patients. Relapse of proteinuria was recorded in 3 patients (at 12, 29, and 34 months). No patients experienced serious adverse events. Rituximab as monotherapy may represent an effective treatment for pure MLN with an excellent tolerance profile. Abstract : Supplemental Digital Content is available in the text